Metanephric adenoma of kidney: a rare case report - Ghosh, Sandeep; Joseph, Bonny; Desai, Sanjay M.; Singh, Soumya; Ghosh, Saurav (International Surgery Journal, 2023)
Metanephric adenoma is a rare benign neoplasm of kidney and is usually a differential diagnosis of Wilms tumor (in children) and papillary renal cell carcinoma (in adults). Here, we present a case report of a 40-year-old gentleman with a right renal mass that was ultimately diagnosed by immunohistochemistry of the final specimen after surgery to be a metanephric adenoma. To prevent needless radical nephrectomies in middle-aged patients metanephric adenoma must be considered in the differential diagnosis of renal mass.